Boundary Objects and Change in Agile Projects - Zaitsev, Anna; Gal, Uri; Tan, Barney (ACIS, 2014)
Agile software development projects utilise different boundary objects in volatile and dynamic project environment. This environment subjects the boundary objects to constant change. The behaviour of boundary objects has not been observed in Agile environment and is thus not well understood. Lack of comprehension can lead to misemployment of boundary objects. This Research-in-Progress describes a case study of a project where two organisations are collaborating to create a software product using Agile methods. The study identifies three different types of boundary objects: temporary, evolutionary and mediating boundary objects. The importance of these three object types to the Agile project is discussed.